2007
DOI: 10.1039/b617800f
|View full text |Cite
|
Sign up to set email alerts
|

Pyrene binding to persistent micelles formed from a dendro-calixarene

Abstract: The formation of micelles of an amphiphilic dendro-calixarene (1) was studied using pyrene as a guest molecule. Steady-state fluorescence experiments were performed, which showed that pyrene is readily solubilized in the micelles and senses an environment with a moderate polarity. Time-resolved fluorescence measurements showed that pyrene in the micelles have two lifetimes, suggesting some compartmentalization of the guest within the micelles. Pyrene bound to the micelles is completely protected from the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 21 publications
4
26
0
Order By: Relevance
“…3,4 At increasing concentration of bile salts, primary aggregates further aggregate to yield loosely held structures, called secondary aggregates and they are stabilized by the hydrogen bonding interaction between the OH group of bile salts and water molecules in the medium (Scheme S1, ESI †). [21][22][23] The binding dynamics of the aggregates is strongly influenced by the ionic strength of the medium and it is well known that the Critical Micellar Concentration (CMC) of the aggregates is decreased along with the increase in the size of the aggregates, as we increase the ionic strength of the medium and the size increase is more prominent in dihydroxy bile salts compared to other trihydroxy salts due to their substantial hydrophobicity. 15,16 However, estimation of the relative amount of bile salts which can be found in different aggregation stages is still a challenging problem and recently, Miranda et al, using fluorescent dansyl derivatives of bile salts, have demonstrated medium dependent aggregation behavior.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 At increasing concentration of bile salts, primary aggregates further aggregate to yield loosely held structures, called secondary aggregates and they are stabilized by the hydrogen bonding interaction between the OH group of bile salts and water molecules in the medium (Scheme S1, ESI †). [21][22][23] The binding dynamics of the aggregates is strongly influenced by the ionic strength of the medium and it is well known that the Critical Micellar Concentration (CMC) of the aggregates is decreased along with the increase in the size of the aggregates, as we increase the ionic strength of the medium and the size increase is more prominent in dihydroxy bile salts compared to other trihydroxy salts due to their substantial hydrophobicity. 15,16 However, estimation of the relative amount of bile salts which can be found in different aggregation stages is still a challenging problem and recently, Miranda et al, using fluorescent dansyl derivatives of bile salts, have demonstrated medium dependent aggregation behavior.…”
Section: Introductionmentioning
confidence: 99%
“…They are formed as aggregates of tailored T-shaped amphiphiles. [1] Such micelles consist of dendrimeric hydrophilic head groups and hydrophobic core groups bound to a central scaffold, which may be a calixarene [1][2][3] or a substituted fullerene. [3][4][5][6] The interaction of ions with surfaces of biological and synthetic nanostructures and their influence on hydrophobic interactions have become the subject of intense current interest.…”
Section: Introductionmentioning
confidence: 99%
“…1 in non-polar solution. A shift at a particular concentration of surfactant has been used to determine the cmc of conventional surfactants (25). The oligoester compounds studied previously are not typical surfactants but do show a change over a fairly broad concentration in the range of 10-50 mM; HO 2 C-Oct-DecOct-G(10)-OH is typical at 33 mM (22).…”
Section: Aggregation In Aqueous Solutionmentioning
confidence: 99%